Tourism and welfare : ethics, responsibility and sustained well-being - Hall, Derek R., (CABI, 2006)
This book provides an explanation, definition and critique of welfare in tourism with regard to issues such as ethics, tourist safety, human rights, ethnocentrism, cultural sensitivity, behaviour codes, green consumerism and perceptions of sustainability. Chapters cover the welfare of tourists, employees in the tourism industry, residents in tourism destinations, pro-poor tourism, animals as tourist attractions and the natural environment. The book has 8 chapters and a subject index.